Post-Islamism And Reform Islamic Law: The Challenges And Future Of Political Islam In Indonesia - Qodir, Zuly (Universitas Islam Negeri Jakarta, 2023)
In Indonesian politics, post-Islamism has emerged in response to the rise of political Islam since the beginning of Reformasi in 1998. Post- Islamism is negotiable and accommodative, seeking to adapt to the Indonesian Archipelago’s political realities and actual social conditions. As such, it does not promote confrontation with political powers—something common in the Islamist movements that gained traction before Reformasi—even as it seeks to counteract the Islamist tendencies that have gained prominence in contemporary Indonesia. This article finds that post-Islamism offers a future in which the political rights of all citizens are guaranteed while social justice and human rights are upheld. Post-Islamists promote neither the formalization of sharia law nor the fundamental transformation of the Indonesian state, but rather a substantive political ideology that welcomes (rather than rejects) democracy. Meanwhile, Islamic law in Indonesia includes sharia laws passed at the provincial and regency levels by the governor or regent (Bupati) with political parties and traders. Although efforts to cultivate post-Islamist mindsets have been hindered by intolerant, exclusive, and extremist elements of Indonesian society, it is hoped that organizations such as Muhammadiyah and Nahdlatul Ulama can continue to maintain a moderate, inclusive and tolerant understanding of Islam. Dalam politik Indonesia, post-Islamisme telah muncul sebagai tanggapan terhadap kebangkitan Islam politik sejak awal Reformasi tahun 1998. Post-Islamisme bersifat negosiatif dan akomodatif, berusaha beradaptasi dengan realitas politik dan kondisi sosial aktual di Indonesia. Dengan demikian, gerakan ini tidak mendorong konfrontasi dengan kekuatan politik, seperti yang umum terjadi pada gerakan Islamis yang mendapatkan daya tarik sebelum Reformasi, bahkan ketika gerakan ini berusaha untuk melawan kecenderungan Islamis yang telah menjadi terkenal di Indonesia saat ini. Temuan artikel ini adalah bahwa Post-Islamisme menawarkan masa depan di mana hak-hak politik semua warga negara dijamin, keadilan sosial ditegakkan, dan hak asasi manusia dijunjung tinggi. Kaum post-Islamis tidak mendukung formalisasi hukum syariah atau transformasi fundamental negara Indonesia, melainkan ideologi politik substantif yang menyambut (dan bukan menolak) demokrasi. Hukum Islam di Indonesia bermanifestasi dalam Perda Syariah Provinsi dan Kabupaten yang disahkan oleh politisi lokal dan gubernur atau bupati yang didukung partai politik dan pedagang. Meskipun upaya untuk mengembangkan pola pikir pasca-Islamisme telah terhalang oleh elemen-elemen masyarakat Indonesia yang intoleran, eksklusif, dan ekstremis, diharapkan organisasi-organisasi seperti Muhammadiyah dan Nahdlatul Ulama dapat terus mempertahankan pemahaman Islam yang moderat, inklusif, dan toleran.